Analysis of Supply Chain Management on Operational Performance of Automotive Companies - Danang Prihandoko; Nayla Nur Alifah (International Journal of Organizational Business Excellence, 2022)
The research aims to determine the influence of supply chain management on the operational performance of the YAMAHA-authorized dealers (YSS) in Bogor and surrounding areas. Respondents to this study were 30 people representing ten YSS. Data collection using questionnaires and analysis using validity test, reliability test, F-test, and multiple regression analysis with the SPSS ver.22. The results of this study indicate that supply chain management has a partial and simultaneous influence on operational performance. Information sharing has a significant effect on operational performance. Long-term relationships have a significant influence on operational performance. Process integration has a significant influence on operational performance, and the delivery system has a significant influence on operational performance at YSS.